2013
DOI: 10.1029/gm126p0261
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Variability of the Thermohaline Circulation in the Past and Future: a Study with a Coupled Model of Intermediate Complexity

Abstract: We present the results of a study of the stability properties of the thermohaline ocean circulation (THC) and the possible mechanisms of rapid climate changes using the climate system model of intermediate complexity, CLIMBER-2. We consider two climate states, the warm modern climate and the cold glacial climate, and compare the stability properties of the THC in both cases. While for modern climate there are two stable circulation modes: the "warm" and the "off" mode, under glacial conditions we find only one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Some authors have suggested that during the last glacial period, North Atlantic air temperatures oscillated in response to changes in strength of the Atlantic meridional overturning circulation (AMOC) when the production of North Atlantic Deep Water (NADW) decreased and(or) shifted to more southerly latitudes causing a decrease in heat exported by surface currents to the North Atlantic region (Ganopolski and Rahmstorf, 2001;Sarnthein et al, 2001;Elliot et al, 2002). Such changes in air temperature would have propagated downwind, influencing the pattern of sea-surface temperature anomalies in the North Pacific Ocean, which, in turn, affected the water-vapor flux to the overlying atmosphere as well as the trajectory of storm systems passing over the Pacific Ocean bringing precipitation to the Great Basin.…”
mentioning
confidence: 99%
“…Some authors have suggested that during the last glacial period, North Atlantic air temperatures oscillated in response to changes in strength of the Atlantic meridional overturning circulation (AMOC) when the production of North Atlantic Deep Water (NADW) decreased and(or) shifted to more southerly latitudes causing a decrease in heat exported by surface currents to the North Atlantic region (Ganopolski and Rahmstorf, 2001;Sarnthein et al, 2001;Elliot et al, 2002). Such changes in air temperature would have propagated downwind, influencing the pattern of sea-surface temperature anomalies in the North Pacific Ocean, which, in turn, affected the water-vapor flux to the overlying atmosphere as well as the trajectory of storm systems passing over the Pacific Ocean bringing precipitation to the Great Basin.…”
mentioning
confidence: 99%